International Wheat Yield Partnership (IWYP) Hub at CIMMYT under WHEAT FP2: A good example of CGIAR/non-CGIAR cross-project learning and translational research - CGIAR Research Program on Wheat (2020)
https://www.dropbox.com/home/Marlo?preview=Annual+Report+Format+IWYP+Hub.docx